2020
DOI: 10.3390/cancers12051125
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine for NSCLC in the Era of Immunotherapy: New Biomarkers to Select the Most Suitable Treatment or the Most Suitable Patient

Abstract: In recent years, the evolution of treatments has made it possible to significantly improve the outcomes of patients with non-small cell lung cancer (NSCLC). In particular, while molecular targeted therapies are effective in specific patient sub-groups, immune checkpoint inhibitors (ICIs) have greatly influenced the outcomes of a large proportion of NSCLC patients. While nivolumab activity was initially assessed irrespective of predictive biomarkers, subsequent pivotal studies involving other PD-1/PD-L1 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 186 publications
(221 reference statements)
2
38
0
1
Order By: Relevance
“…In addition, through the activation of the antigen presentation process and anticancer cellular immunity, ARID1A and ARID1B deficiencies could modulate the TIME of NSCLC and initiate a therapeutic immune reaction to tumors. In this research, we confirmed the important role of ARID1A deficiency in elevating cancerous mutability and changing tumors to exhibit an aggressive phenotype in NSCLC, which was proposed by published works (Shen et al 2018 ; Jiang et al 2020 ; Okamura et al 2020 ; Rossi et al 2020 ) on other cancer types. Additionally, our research is the first to investigate the role of ARID1B, which is another ARID1 subunit similar to ARID1A, in changing the phenotype of cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, through the activation of the antigen presentation process and anticancer cellular immunity, ARID1A and ARID1B deficiencies could modulate the TIME of NSCLC and initiate a therapeutic immune reaction to tumors. In this research, we confirmed the important role of ARID1A deficiency in elevating cancerous mutability and changing tumors to exhibit an aggressive phenotype in NSCLC, which was proposed by published works (Shen et al 2018 ; Jiang et al 2020 ; Okamura et al 2020 ; Rossi et al 2020 ) on other cancer types. Additionally, our research is the first to investigate the role of ARID1B, which is another ARID1 subunit similar to ARID1A, in changing the phenotype of cancer.…”
Section: Discussionsupporting
confidence: 87%
“…As is well known, the PD-L1 expression or TMB level did not disclose satisfied efficiency in selecting patients who might benefit from immunotherapy while plasma NGS circulating-free DNA (cfDNA) analysis in NSCLC might provides new biomarkers for cancer immunotherapy (Rossi et al 2020 ). According to the previous studies, the co-mutations of TP53 and STK11 serve as an important role in modulating the TIME of NSCLC and related to the sensitivity to ICIs treatment (Skoulidis and Heymach 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, through the activation of the antigen presentation process and anticancer cellular immunity, ARID1A and ARID1B de ciencies could modulate the TIME of NSCLC and initiate a therapeutic immune reaction to tumors. In this research, we con rmed the important role of ARID1A de ciency in elevating cancerous mutability and changing tumors to exhibit an aggressive phenotype in NSCLC, which was proposed by published works [16][17][18]26] on other cancer types. Additionally, our research is the rst to investigate the role of ARID1B, which is another ARID1 subunit similar to ARID1A, in changing the phenotype of cancer.…”
Section: Discussionsupporting
confidence: 60%
“…As is well known, the PD-L1 expression or TMB level did not disclose satis ed e ciency in selecting patients who might bene t from immunotherapy while plasma NGS circulating-free DNA (cfDNA) analysis in NSCLC might provides new biomarkers for cancer immunotherapy [26]. According to the previous studies, the co-mutations of TP53 and STK11 serve as an important role in modulating the TIME of NSCLC and related to the sensitivity to ICIs treatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tumors with high microsatellite instability (MSI-H) also have a higher tumor mutation burden, indicating that there is a certain correlation between them. Moreover, a series of experimental studies have confirmed that tumor infiltrating lymphocytes (TILs), neutrophil-to-lymphocyte ratio (NLR), electronic nose analysis of exhaled breath and other biomarkers can help to screen patients who can benefit from immunotherapy for NSCLC ( Tokito et al., 2016 ; de Vries et al., 2019 ; Lee and Ruppin, 2019 ; Rossi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%